Design and Synthesis of 2,6-Disubstituted-4'-Selenoadenosine-5'-N,N-Dimethyluronamide Derivatives as Human A3 Adenosine Receptor Antagonists - Hongseok Choi; Kenneth A. Jacobson; Jinha Yu; Lak Shin Jeong (MDPI AG, 2021)
A new series of 4'-selenoadenosine-5'-N,N-dimethyluronamide derivatives as highly potent and selective human A3 adenosine receptor (hA3AR) antagonists, is described. The highly selective A3AR agonists, 4'-selenoadenosine-5'-N-methyluronamides were successfully converted into selective antagonists by adding a second N-methyl group to the 5'-uronamide position. All the synthesized compounds showed medium to high binding affinity at the hA3AR. Among the synthesized compounds, 2-H-N6-3-iodobenzylamine derivative 9f exhibited the highest binding affinity at hA3AR. (Ki = 22.7 nM). The 2-H analogues generally showed better binding affinity than the 2-Cl analogues. The cAMP functional assay with 2-Cl-N6-3-iodobenzylamine derivative 9l demonstrated hA3AR antagonist activity. A molecular modelling study suggests an important role of the hydrogen of 5'-uronamide as an essential hydrogen bonding donor for hA3AR activation.